2010
DOI: 10.1021/bi901864j
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Prereaction State of Pyruvate Decarboxylase from Zymomonas mobilis,

Abstract: Pyruvate decarboxylase (PDC) uses thiamine diphosphate as an essential cofactor to catalyze the formation of acetaldehyde on the pathway of ethanol synthesis. Here we report the crystallographic image of a prereaction intermediate of a bacterial pyruvate decarboxylase prepared by cocrystallizing the enzyme with pyruvate and a stable analogue of the cofactor’s activated ylid form. A second crystal structure of PDC in complex with fluoride shows that the ion organizes a water molecule that occludes the pyruvate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 50 publications
2
41
0
1
Order By: Relevance
“…The alignment also confirmed conservation of the localization of the four ionizable residues in PDC and IPDC proteins (Asp30; His116; His117; Glu481), which seem to play a more prominent role in catalysis than in substrate binding (Andrews and McLeish, 2012). The established 3D structures of pyruvatecomplexed Z. mobilis PDC (PDB ID 2wva; Pei et al 2010) and E. cloacae IPDC (PDB ID 1ovmA; Schütz et al 2003b) were used to infer the size of the active site of P. serpens enzyme and the location of potentially important residues (Fig. 6).…”
Section: Structural Characteristics Of the Active Site Of P Serpens supporting
confidence: 52%
See 1 more Smart Citation
“…The alignment also confirmed conservation of the localization of the four ionizable residues in PDC and IPDC proteins (Asp30; His116; His117; Glu481), which seem to play a more prominent role in catalysis than in substrate binding (Andrews and McLeish, 2012). The established 3D structures of pyruvatecomplexed Z. mobilis PDC (PDB ID 2wva; Pei et al 2010) and E. cloacae IPDC (PDB ID 1ovmA; Schütz et al 2003b) were used to infer the size of the active site of P. serpens enzyme and the location of potentially important residues (Fig. 6).…”
Section: Structural Characteristics Of the Active Site Of P Serpens supporting
confidence: 52%
“…The overall quality of the models was assessed by Ramachandran plots using the RAMPAGE server (Lovell et al 2003). PyMOL (http://www.pymol.org) was used to visualize and align the established three-dimensional structures of E. cloacae IPDC (PDB ID 1ovmA, Schütz et al 2003b) and Z. mobilis PDC (PDB ID 2wva, Pei et al 2010).…”
Section: Sequence Alignment and Modellingmentioning
confidence: 99%
“…By virtue of the neutral ring in place of the positively charged thiazolium ring, the authors suggested that this would serve as an electrostatic mimic of the carbene [57,58]. Later the thiazolium ring was replaced by a triazole ring in yet a different mimic of a neutral 5-membered ring [59].…”
Section: The C2-carbanion/ylide/carbenementioning
confidence: 99%
“…It is of interest to note that there was more AlcDH (spots 417, 418, 419 and 420), but less AldDH (spots 335, 336, 337 and 338)-this would suggest A100-8 produces more kinds of ethanols. Pyruvate decarboxylase (spots 158, 159, 160, 161 and 162) was more abundant in A100-8, and uses thiamine diphosphate as an essential cofactor to catalyze the formation of acetaldehyde in ethanol synthesis [42,43]. The over-production of ethanol is beneficial in the formation of flavor products such as esters.…”
Section: Peptides Involved In Amino Acid Metabolism and Secondary Metmentioning
confidence: 99%